The resveratrol analogue trimethoxystilbene inhibits cancer cell growth by inducing multipolar cell mitosis. Issue 3 (24th October 2016) - Traversi, Gianandrea; Fiore, Mario; Percario, Zulema; Degrassi, Francesca; Cozzi, Renata
Abstract : Natural compounds are extensively studied for their potential use in traditional and non‐traditional medicine. Several natural and synthetic Resveratrol analogues have shown interesting biological activities in the field of cancer chemoprevention. In the present study, we have focused on the ability of Resveratrol and two methoxylated derivatives (Trimethoxystilbene and Pterostilbene) to inhibit human cancer cell growth particularly analyzing their ability to interfere with tubulin dynamics at mitosis. We show that Trimethoxystilbene, differently from Resveratrol and Pterostilbene, alters microtubule polymerization dynamics in HeLa cells specifically inducing multipolar spindles and mitotic arrest coupled to a reduction of cell growth and an increase in apoptotic death by mitotic catastrophe. This work demonstrates that the structural modification of Rsv causes substantial changes in the mechanism of action of the derivatives. The presence of three extra methyl groups renders Trimethoxy very efficient in impairing cell proliferation by inducing mitotic catastrophe in cancer cells. © 2016 Wiley Periodicals, Inc.